INVESTIGATING THE IMPACT OF STORY MAPS IN DEVELOPING STUDENTS' SPATIAL ABILITIES ON HYDROMETEOROLOGICAL DISASTERS FOR E-PORTFOLIO ASSIGNMENTS - Rizcha Tasliya; Eldina Fatimah; Muksin Umar (RADJA PUBLIKA, 2023)
The government of Indonesia has issued a self-study curriculum for colleges based on the principles of the Fourth Industrial Revolution in the digital age. The new rule recommends an online portfolio as a tool for measuring the success of educational programs. Students at Syiah Kuala University (USK) utilized Story Map electronic portfolios to hone their spatial skills in the General Compulsory Course on Disaster and Environmental Knowledge. This study aims to improve upon the concept of the Story Map and use it as a component of students' electronic portfolios in order to evaluate their capacity to plan for and respond to hydrometeorological disasters. The concept of the Story Map is created as a digital portfolio project, beginning with secondary materials including literature studies, raster and vector data from ESRI and Mapbox. The ability to perceive spatial relationships is measured by collecting primary data in the form of a questionnaire. The findings of a F (Simultaneous) statistical test for testing hypotheses are as follows: With Fcount > Ftable = 228.338 > 3.34, we get a value of F = 0.000<0.05. Both e-portfolios and narrative maps impact students' spatial abilities in relation to hydrometeorological disasters, as shown by the F test scores. T-tests for multiple variables Students' spatial intelligence is affected by the narrative map (X1) in the proportion of 4.746 > Tcount > Ttable. 2.048. The e-portfolio variable (X2) has a positive effect on students' spatial abilities (Y), with a value of Tcount > Ttable, or 14.063 > 2.048..